Pengaruh Citra Merek, Harga, dan Promosi Produk Pada Minat Beli Produk Mixue Ice Cream & Tea di Kabupaten Purwakarta - Qibtiyah, Desy; Fitriani, Anisa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Achmad Yani Yogyakarta, 2023)
The development of the culinary business is increasing from year to year, forcing companies to maintain a competitive advantage. This is important so that its products can survive among emerging competitors. This study examines one of the companies engaged in the food and beverages that are very popular today, namely Mixue Ice Cream & Tea. Mixue Ice Cream & Tea was established in 1997 in China and had many outlets in Indonesia, one of which is in Purwakarta Regency, West Java Province. This study aimed to see the effect of brand image, price and product promotion of Mixue Ice Cream & Tea on consumer buying interest. This study uses a quantitative approach with a probability sampling technique. The analysis was conducted using PLS-SEM on 31 consumer students in Purwakarta Regency, West Java Province students. The findings in this study indicate that brand image and promotion variables significantly affect consumer buying interest, while price has no significant effect on consumer buying interest.